The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2019
DOI: 10.4149/bll_2019_142
|View full text |Cite
|
Sign up to set email alerts
|

Association between hemogram‑derived indices and culture‑positive infections in intensive care population

Abstract: AIM: To investigate the relationship between hemogram parameters and bacterial growth in cultures of blood, urine or sputum in intensive care unit patients. METHODS: This retrospective, observational, cross-sectional study was conducted in a tertiary referral hospital between March 2015 and December 2017. Baseline demographic and clinical characteristics, hemogram parameters and other laboratory test results of patients admitted to intensive care unit were recorded. Patients were divided into two groups as pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Although the values for CRP were also similar, the prognostication using this parameter was much better in our cohort (AUC = 0.62; 95% CI 0.54–0.70 vs. 0.86; 95% CI 0.8–0.92). NLR and PLR were significant predictors of infection in a comparable cohort of intensive care patients in Turkey [ 18 ]. However, the values of NLR, PLR as well as CRP and PCT in their study were completely incomparable with our data, which makes the comparison impractical.…”
Section: Discussionmentioning
confidence: 99%
“…Although the values for CRP were also similar, the prognostication using this parameter was much better in our cohort (AUC = 0.62; 95% CI 0.54–0.70 vs. 0.86; 95% CI 0.8–0.92). NLR and PLR were significant predictors of infection in a comparable cohort of intensive care patients in Turkey [ 18 ]. However, the values of NLR, PLR as well as CRP and PCT in their study were completely incomparable with our data, which makes the comparison impractical.…”
Section: Discussionmentioning
confidence: 99%
“…When combined the inflammatory markers with either PLT or PMR, the combinational diagnostic sensitivity and specificity reached 90%, which somehow supported the results reported by Tirumala et al Despite the previously studied PLT and PMR, we investigated the utility of another platelet-related marker, plateletcrit (PCT), for diagnosing PJI. Increased level of PCT has been reported to be associated with infection and hospital mortality in intensive care unit patients [30,31]. For the first time, we evaluated its possibility for diagnosing PJI.…”
Section: Discussionmentioning
confidence: 99%
“…have been increasingly reported to be infectious agents in inpatients and have caused outbreaks in ICUs 3 , 5 , 10 . Yoldas et al 12 showed that more than 10% of the microbial growth in clinical cultures were Gram-positive bacteria cultured from ICU patients.…”
Section: Discussionmentioning
confidence: 99%